On the analysis of masonry structures without box behavior - Lourenço, Paulo B. (2011)
Assessment of the seismic performance of structures is still challenge. Historic masonry structures exhibit peculiar properties (low tensile strength and lack of box behavior) that make the task of the analyst even more difficult. It seems that traditional design and assessment methods, similar to the ones currently used for reinforced concrete structures, are not applicable. This paper provides a review of the seismic analysis of masonry structures without box behavior. Different methods of structural analysis are discussed and a comparison is made between pushover methods and non-linear dynamic analysis with time integration. Three cases studies (S. Torcato church, Qutb Minar and “Gaioleiros” buildings) were used and the results show that traditional, adaptive or modal pushover analyses are not totally in agreement with non-linear dynamic analysis or experimental observations, namely cycle and rigid block behavior (rocking) and the out-of-plane behavior.